Effectiveness and Safety of a Paclitaxel-Eluting Stent for Superficial Femoral Artery Lesions up to 190 mm: One-Year Outcomes of the Single-Arm IMPERIAL Long Lesion Substudy of the Eluvia Drug-Eluting Stent. (April 2020) - Golzar, Jaafer; Soga, Yoshimitsu; Babaev, Anvar; Iida, Osamu; Kawasaki, Daizo; Bachinsky, William; Park, James; Prem, Jeffery T.; Vermassen, Frank; Diaz-Cartelle, Juan; Müller-Hülsbeck, Stefan; Gray, William A.
Purpose: To report the clinical effect of a drug-eluting stent on femoropopliteal occlusive disease in patients with long lesions.Materials and Methods: The global IMPERIAL Long Lesion substudy ( ClinicalTrials.gov identifier NCT02574481) is a prospective, single-arm, multicenter trial of the Eluvia Drug-Eluting Vascular Stent for treating femoropopliteal lesions >140 mm and ≤190 mm in length. Fifty patients (mean age 68.2 years; 32 men) with long lesions (mean length 162.8±34.7 mm) were enrolled; 20 patients had diabetes. Fourteen of the lesions were severely calcified and 16 were occluded. Primary patency (duplex ultrasound peak systolic velocity ratio ≤2.4 in the absence of clinically-driven target lesion revascularization or bypass of the target lesion) and major adverse events [30-day all-cause death and 1-year target limb major amputation or target lesion revascularization (TLR)] were assessed at 12 months.Results: At 12 months, no deaths, target limb amputations, or stent thrombosis had occurred. The Kaplan-Meier estimate of primary patency was 91.0% (95% CI 82.5% to 99.6%). The MAE-free rate at 12 months was 93.5% due to 3 clinically-driven TLRs. The corresponding Kaplan-Meier estimate of freedom from TLR was 93.9% (95% CI 87.2% to 100%).Conclusion: The IMPERIAL Long Lesion substudy demonstrated excellent patency and safety through 1 year among patients with long femoropopliteal occlusive disease treated with the Eluvia stent.